Autotaxin and chronic inflammatory diseases. (November 2019) - Magkrioti, Christiana; Galaris, Apostolos; Kanellopoulou, Paraskevi; Stylianaki, Elli-Anna; Kaffe, Eleanna; Aidinis, Vassilis
Abstract: Autotaxin (ATX) is a secreted glycoprotein, widely present in biological fluids including blood. ATX catalyzes the hydrolysis of lysophosphatidylcholine (LPC) to lysophosphatidic acid (LPA), a growth factor-like, signaling phospholipid. LPA exerts pleiotropic effects mediated by its G-protein-coupled receptors that are widely expressed and exhibit overlapping specificities. Although ATX also possesses matricellular properties, the majority of ATX reported functions in adulthood are thought to be mediated through the extracellular production of LPA. ATX-mediated LPA synthesis is likely localized at the cell surface through the possible interaction of ATX with integrins or other molecules, while LPA levels are further controlled by a group of membrane-associated lipid-phosphate phosphatases. ATX expression was shown to be necessary for embryonic development, and ATX deficient embryos exhibit defective vascular homeostasis and aberrant neuronal system development. In adult life, ATX is highly expressed in the adipose tissue and has been implicated in diet-induced obesity and glucose homeostasis with multiple implications in metabolic disorders. Additionally, LPA has been shown to affect multiple cell types, including stromal and immune cells in various ways. Therefore, LPA participates in many processes that are intricately involved in the pathogenesis of different chronic inflammatory diseases such as vascular homeostasis, skeletal and stromal remodeling, lymphocyte trafficking and immune regulation. Accordingly, increased ATX and LPA levels have been detected, locally and/or systemically, in patients with chronic inflammatory diseases, most notably idiopathic pulmonary fibrosis (IPF), chronic liver diseases, and rheumatoid arthritis. Genetic and pharmacological studies in mice have confirmed a pathogenetic role for ATX expression and LPA signaling in chronic inflammatory diseases, and provided the proof of principle for therapeutic interventions, as exemplified by the ongoing clinical trials for IPF. Highlights: Autotaxin is largely responsible for the bulk of extracellular LPA production. LPA exerts pleiotropic effects mediated by its G-protein-coupled receptors. Increased ATX and LPA levels have been detected in chronic inflammatory diseases. Genetic and pharmacologic studies in mice suggest ATX as a therapeutic target.